Overview of health-saving skills developing technologies - Tulakpayeva, S.S.; Aitkulov, A.M.; Zhuzbaeva, G.O. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article reviews and compares the diversity of health-saving skills developing technologies in different studies of educational process, that provide knowledge and skills to maintain well-being of students. First year students face challenges that are threatening their physical and mental health, and undergo the new selfdestroying habits like smoking, drinking, alcohol, depravation of sleep, bad nutrition etc. First year students’ adaptation should be followed with attention to develop independent health-saving skills. The technologies developing health-saving skills, like researched-based programs, theoretical base and skills are reviewed and widely examined. The article contains analyzed information on health-saving skills, methods of developing health-saving skills, socioeconomic status and health-related quality of life, and use health-related quality of life (HRQOL) as criteria to differentiate level of impact on academic success of students. The role of efficient and promising technologies of developing health-saving skills on changing attitude about wellbeing and health, bringing understanding among freshman students about influence of health on academic success and other aspects of life is overviewed. Compared technologies developing health-saving skills affect academic success of students on the different level of approach, and it concludes that for a great change, it is better to use skill-based method.
Денсаулық сақтау дағдыларын қалыптастыру технологияларына шолу
Обзор технологий формирования здоровьесберегающих навыков
Keywords: health-saving skills; skilled-based education; research-based programs; theory-based education; physical and mental health; first year students